Chest Tube Drainage Under Radiological Guidance for Pleural Effusion and Pneumothorax in a Tertiary Care University Teaching Hospital: Review of 51 Cases - Luce Cantin; Carl Chartrand-Lefebvre; Luigi Lepanto; David Gianfelice; Antoine Rabbat; Benoît Aubin; Pierre Perreault; Renée Déry; Michel Lafortune (Canadian Respiratory Journal)
BACKGROUND: Chest tube drainage under radiological guidance has been used with increasing frequency as a treatment option for pleural effusions and pneumothoraxes.